DETERMINATION OF FERMENTATION LENGTH AND INITIAL pH OF MEDIA IN PRODUCING ETHANOL BY BM1-CP14 - Pranidhani, Ida Ayu Somya Iswari; Wijaya, I Made Mahaputra; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
This study aims to determine the optimum duration of fermentation and the best initial pH of the growth medium BM1-CP14 isolates in order to producing ethanol. In this study, 5 treatments of fermentation time (2, 4, 6, 8 and 10 days) combined with 3 initial pH treatments of the fermentation medium (4, 5, and 6) were conducted. This research was carried out in several step, namely cell rejuvenation, propagation of BM1-CP14 isolates, fermentation, distillation, and calculation of total ethanol. The best fermentation duration was found to be 10 days with difference of total dissolved solid 1.07 (?%brix) yielded total ethanol of 5.08 mL. In the initial pH treatment, the media produced total ethanol at pH 4 of 5.15 mL, pH 5 of 5.17 mL and pH 6 of 5.16 mL. The pH treatment of BM1-CP14 bacteria was found to have no effect due to the total ethanol produced was almost similar.